Episodic future thinking modulates delay discounting in individuals with problematic substance use: a narrative review - Chen, Xiwen; Wang, Huanxin; Fan, Cong (Frontiers in Psychiatry, 2026)
Substance use disorder (SUD) poses significant challenges to public health, the economy, and social safety. Delay discounting (DD) is one form of impulsivity which is a risk factor for SUD and other mental health disorders. Moreover, when faced with immediate rewards, individuals with SUD exhibit increased DD compared to healthy controls. Fortunately, previous studies have shown that EFT, referring to vividly imagining potential future events in specific scenarios based on an individual’s current experiences, can effectively reduce DD and substance use in individuals with SUD. In this process, the potential regulatory mechanism of EFT may involve extending the temporal window and decreasing the construal level of future events. Most promising avenues to pursue in future studies may include manipulating participants’ factors (e.g., sample size, adherence to diagnostic criteria, comorbidity with other mental diseases), conducting longitudinal studies and exploring the neural regulatory mechanisms of EFT on DD among individuals with SUD. Further research should also examine the effects of both positive and negative emotional valence in EFT interventions to determine how different types of future thinking influence impulsivity and decision-making. This would help us develop more applicable theoretical models and improve the effectiveness of EFT in intervening with SUD.